(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
The study demonstrates the educational ideas and didactic innovations of the distinguished Italian educator, Giuseppe Lombardo Radice. The activities of Lombardo Radice is unknown in Hungary. In 1923 he took part in the elaboration of the educational reform and introduced several innovations in elementary schools. The methodology of his programmes is novel: it was the end of encyclopedism and formalism. Lomhardo Radice pedagogy is still present in Italy as the pedagogy of curiosity, experimenting and freedom.